Potential and challenges in up-scaling micro-irrigation in India: experiences from nine states. - Kuppannan, Palanisami; Raman, S. (International Water Management Institute, 2012)
Studies from nine states indicate that adoption of micro-irrigation (MI) technologies - drip and sprinkler systems - has a positive impact in terms of water saving, yield and income enhancement at farm level. However, the overall impression among the farmers is that MI is capital intensive and suited only to large farmers who have Access to capital and technical knowhow. As such, only 12.2 percent of potential drip irrigation area and 7.8 percent of potential sprinkler area is covered in the country with large variations across states. Majority of the MI adopters we sampled in Andhra Pradesh, Karnataka, Orissa and Punjab were small farmers. In contrast, in Maharashtra and Tamil Nadu, majority of MI adopters we found were large farmers. Analysis of the rate of return on MI investment indicated no significant difference in incremental net income attributed to MI across farm categories; however, there were significant differences in incremental net income of MI adopters across States. For accelerating MI adoption in the country, the recommendations include reduction in capital cost of the system, provision of technical support for regular MI operation and maintenance, relaxation of farm size limitation in providing MI subsidies and creation of a single state level agency or a Special Purpose Vehicle (SPV) for speedy implementation of the MI program.